An application of the k-means clustering method to National Public Safety Data - the case of intentional homicides - Alves, Henrique José de Paula; Fernandes, Felipe Augusto; Silva, Édipo Menezes da; Batista, Ben Dêivide de Oliveira (Brazilian Journal of Biometrics, 2025)
The purpose of this article is to assist Brazilian authorities in directing resources to reduce the rate of intentional homicide per 100,000 inhabitants in the federative units of Brazil. In this sense, linked to the information made available by the National Secretariat for Public Security (Senasp), it was decided to apply the grouping technique known as k-means to group the FU’s by similar rates. Three clusters were found and, then, a detailed description of each of the FU’s belonging to each of the three clusters was carried out. We noticed that only the FU’s that form cluster 1 have a homicide rate below 16 victims per 100,000 inhabitants, the limit imposed by the 2021 National Public Security Plan.. This plan was prepared by Brazilian Ministry of Justice, Senasp and state public security departments. The information provided by Senasp was accounted for in the period from 2015 to 2022 and the rates were calculated, in the usual way, for each year.